Case of delayed diagnosis of necrolytic migratory erythema. Issue 12 (11th December 2021) - Abdelli, Wissal; Alaoui, Fatima; Souissi, Asmahen; Sassi, Wiem; Chelly, Ines; Haouet, Slim; Mokni, Mourad
Abstract: Necrolytic migratory erythema (NME) is a rare cutaneous paraneoplastic manifestation of glucagonoma. We report a case of a woman with a 6‐year history of delayed diagnosis of glucagonoma. This case highlights the atypical clinical features of NME which makes the diagnosis difficult. Abstract : Necrolytic migratory erythema is rare. It presents typically as an annular‐circinate, erythematous, scaly rash. Our patient's lesions were deceptive mimicking eczema, prurigo, or insect bites. Our case highlights the atypical clinical features of necrolytic migratory erythema which makes the diagnosis difficult. Dermatologists must be aware of this condition subsequently they can be the first physician to suspect it.